Comunicación simultánea: un modelo para enfrentar los déficit lingüísticos del niño autista - Puras Tellaeche, Socorro (1985)
The use os simultaneous communication methods for the treatment of autistic children is one of the most promising ways for increasing the communicative competence of these children. In this paper, the results of the treatment of two autistic children with simultaneous communication methods and its implications are revised.